Attribution of Mental States in Glossolalia: A Direct Comparison With Schizophrenia - Kéri, Szabolcs; Kállai, Imre; Csigó, Katalin (Frontiers in Psychology, 2020)
Glossolalia (“speaking in tongues”) is a rhythmic utterance of pseudo-words without consistent semantic meaning and syntactic regularities. Although glossolalia is a culturally embedded religious activity, its connection with psychopathology (e.g., psychotic thought disorder and altered mental state attribution/mentalization) is still a matter of debate. To elucidate this issue, we investigated 32 glossolalists, 32 matched control participants, and 32 patients with schizophrenia using the Animated Triangles Test (ATT) and the Reading the Mind in the Eyes Test (RMET). The ATT can detect hypo- and hypermentalization using animations of two moving triangles. Healthy adults describe these as random movements (e.g., bouncing), willed actions (e.g., playing), or they mentalize (e.g., tricking). We found that glossolalists provided more mentalizing descriptions in the ATT random and intentional movement animations relative to the control participants. They also recognized more mental states on the RMET than the controls. None of them had a diagnosis of mental disorders. In contrast, patients with schizophrenia hypermentalized only in the ATT random movement condition, whereas they showed hypomentalization in the ATT intentional movement condition and in the RMET relative the control subjects. Hypermentalization in the ATT positively correlated with intrinsic religiosity in the glossolalia group. In conclusion, our results demonstrated a substantial difference in the mentalizing ability of glossolalists (generalized hypermentalization) and patients with schizophrenia (both hypo- and hypermentalization).